Factors that Affect High School Students Making Them Not Like Mathematics: https://doi.org/10.69692/SUJMRD0802250 - LILIANOU, Lisatteur; PHANALASY , Oudone; VONGBOUNSY , Parnthong; BOUNPHONE , Khammai; THANAVANH, Pinkham (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research paper explores the factors that make high school students reluctant to study mathematics, which aims to: 1) analyze the general information of the sample; 2) Analyze the external factors that make high school students reluctant to study mathematics; 3) Analyze the internal factors that make high school students reluctant to study mathematics; 4) Prioritize the factors that affect the students' reluctance to study mathematics. The sample used in the research was six high school students in Vientiane Capital and Vientiane Province, who interviewed 1,587 students. The research tools were questionnaires, and the data were analyzed using Analytic Hierarchy Process Model. From the sample group of students, it found that there was female more than males. The external factors that make students not like to study mathematics are due to the difficulty, inadequate mathematics textbooks, usefulness of mathematics in daily life, teachers lacking knowledge, families do not support, society does not pay attention to mathematics, mathematics is not interesting and schools do not pay attention to mathematics. The internal factors that make students not like mathematics are: the method of teaching with new ideas that students are interested and understand easily the concept of mathematics levels at intermediate, the curriculum factor determining the content of the mathematics levels intermediate, the factor in the teaching and learning media making the students creative and rational levels at intermediate. The building factor has not enough books for students to read is at the high level, the family factor is the family encourages doing business is at high level, the social factor is the students often go to the market or the city and the village without a definite purpose is at high level, the environmental factor is students using smart phones is at the highest level, and the economic factor of family is the students having pocket money for schools is at the highest level. The factors that make high school students reluctanting to study mathematics are ordered from high to low as environmental factor, social factor, building factor, curriculum factor, teacher teaching factor, family factor, teaching-learning media factor and economic factors, respectively.